Thomas Ewing Jr frontier lawyer and Civil War general - Smith, Ronald D., 1947- (University of Missouri Press, 2008)
"Examines Thomas Ewing Jr.'s career as a real estate lawyer, judge, soldier, and speculator in Kansas and how he came to national prominence in the fight over the proslavery Lecompton Constitution, was instrumental in starting the Union Pacific Railroad, and became the first chief justice of the Kansas Supreme Court"--Provided by publisher.